Channel Estimation for Millimeter Wave Cellular Systems - Nakhaei, Sepehr Ashtari (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
The imagination of our future on wireless base networks is beyond science fiction. By emerging 2020, most of the wireless communication systems are going to suffer by the vast increase in the number of traffic in their network which leads to the lower data rate and higher latency. The current cellular network provides the stable connection for the demanding users, but in near future this technology will need a drastic improvement as it crosses its capabilities when users want more data. Therefore, 4G is going to be replaced by 5G. 5G technology, which is currently under development, is going to achieve a couple of objectives such as higher spectral efficiency, preferable battery life for handsets, higher capacity, improvement in the coverage area and lower latency. For this technology, to be realistic and operative as it is promised, some upcoming technologies such as massive MIMO, millimeter wave, beamforming and small cells are going to aid 5G system. Millimeter wave along with massive MIMO provides a high data rate within a large coverage area. Additionally, beamforming manages the massive transmission of data to all over the medium and directs the data to a specific user. In every wireless network, there are losses due to the propagation of medium, also known as channel. The channel is usually estimated by the signal processing module to assist the receiver in order to eliminate channel’s severe domination. For each generation of wireless cellular networks, a model by all the factors that have an impact on the signal will be presented as a fixed modeled and then channel is estimated and compared to the modeled version to have constancy. 5G network channel should be carefully estimated due to the use of high frequency band and the massive number of antennas. In this thesis, our focus is on estimation of channel through some training procedures. We try to pre-code the incoming input signal with some code words to reach as close as possible to the actual channel. Accordingly, BER, MSE and spectral efficiency will be illustrated to provide the channel performance and stability of the mm-wave systems. Keywords: 5G, Beamforming, Channel estimation, Precoding, Massive MIMO, Millimeter Wave and Small Cells.

ÖZ: Kablosuz ağlar üzerine kurulan hayaller bilim kurgunun ötesine geçmiş durumdadır. 2020 yılının yaklaşmasıyla beraber, birçok kablosuz haberleşme sistem ağlarında geniş çapta bir trafik artışından ötürü sıkıntı yaşanacaktır. Bundan dolayı veri hızında düşüş ve gecikmelerde artış gözlemlenecektir. Mevcut hücresel ağlar, kullanıcıların taleplerine yanıt verebilmektedir fakat yakın gelecekte bu teknolojilerin ciddi bir şekilde gözden geçirilip, kullanıcıların daha fazla veriye ihtiyaç duyacakları an için hazır hale getirilmeleri gerekmektedir. Bu gibi sebeplerden ötürü 5G sistemlerinin 4G’nin yerine geçmesi öngörülüyor. Şuan gelişme aşamasında olan 5G teknolojisinin ulaşması gereken bir takım hedefler bulunmaktadır. Bu hedeflerden öne çıkanlar yüksek spektrum verimliliği, taşınabilir cihazlar için pil ömründe artış, yüksek veri hızı, yüksek kapasite, kapsama alanında artış ve gecikmede düşüş olarak sıralanabilir. Bu teknoloji söz verildiği şekilde işlevsel olabilmesi için şuan gelişme aşamasında olan bazı teknolojilere ihtiyaç duymaktadır. 5G sistemleri, yoğun çokgirdili çok-çıktılı sistem, milimetre dalga, huzme oluşturma ve küçük hücreler gibi yeni teknolojilerin birleşmesiyle oluşturulacaktır. Milimetre dalga teknolojisinin yoğun çok-girdili çok-çıktılı sistem ile birleşmesiyle birlikte veri hızında ve kapsama alanında artış sağlanacaktır. Ayrıca, huzme oluşturma teknolojisi ise ortamdaki yoğun veri akışını düzenleyip, bu veriyi gönderilmek üzere belirlenmiş olan kullanıcıya yönlendirecektir. Tüm kablosuz haberleşme ağlarında ortamdaki yayılmadan ötürü kanal olarak adlandırılan kayıplar yaşanmaktadır. Genellikle kanalın etkisine son verip vericiye yardım etmek için bir takım sinyal işleme metotları ile kanal kestirimi yapılmaktadır. Kablosuz hücresel ağların her kuşakta sinyale etki eden bazı parametreleri vardır ve bu gibi parametreler sabit model olarak adlandırılır. Kanal kestirimi ise bu parametreler üzerinden yapılır ve tutarlı olabilmesi için modellenen kanal ile kıyaslanır. 5G sistemlerinde çok yüksek frekans bandı ve anten sayısı kullanıldığından kanal kestirimi büyük önem taşımaktadır. Bu tezde yoğunlaşılan nokta, belli bir hazırlık prosedürüne tabi tutulan kanal kestirimidir. Bu amaç doğrultusunda gelen giriş sinyaline ön-kod çalışması yapılarak var olan kanala olabildiğince yakın bir kanal kestirimi elde edilmeye çalışılmıştır. Sonrasında ise bit hata oranı, ortalama karesel hata ve spektral verimlilik gibi parametreler hesaplanarak kanal performansı ve milimetre dalga sistemlerinin kararlılığı gösterilmiştir. Anahtar Kelimeler: 5G, huzme oluşturma, kanal kestirimi, ön kodlama, yoğun çokgirdili çok-çıktılı sistem, milimetre dalga, küçük hücreler
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2018. Co-Supervisor: Assoc. Prof. Dr. Ali Hakan Ulusoy. and Supervisor: Assoc. Prof. Dr. Ahmet Rızaner.
Keywords: Electrical and Electronic Engineering; Radar transmitters; 5G; Beamforming; Channel estimation; Precoding; Massive MIMO; Millimeter Wave and Small Cells